THE EFFECT OF COMPLEXITY IN ORGANIZATION AND JOB INVOLVEMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) OF PRIMARY SCHOOL TEACHERS IN DUREN SAWIT SUB DISTRICT - Ningtyas, Septiana Ika (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2016)
Abstract: The objective of this research was to understand the effect of complexity in organization and job involvement on OCB. It was a quantitative research was conducted in seven schools located in Duren Sawit Sub District, East Jakarta. The research uses a survey method with path analysis was applied in testing hypothesis. It was conducted to 70 teachers at Primary School as the respondents which were selected in a simple random way. The result of this study are : (1). There is a positive direct effect of complexity in organization on OCB. (2). There is a positive direct effect of job involvement on OCB, and (3). There is a positive direct effect of complexity in organization on job involvement.Keywords: complexity in organization, job involvement, organizational citizenship behavior (OCB).